Challenges and Prospects of Applying the Paradigm of Sustainable Development to the Eastern Europe Economy - Kulinich, Tetiana; Yakimenko-Tereschenko, Natalia; Melnyk, Alla; Vasina, Alla; Adamyk, Viktoriia (Unifying Science and Engineering, 2021)
The paradigm of sustainable development for the economy of Eastern Europe needs detailed research challenges and prospects in Global Sustainable Development Goals implementation by 2030. The main section of the study shows the results determining the position of Eastern European countries on the levels of implementation of the sustainable development concept. The purpose of the study is to analyze existing one’s challenges and prospects of applying the paradigm of sustainable development to the economy of Eastern Europe, by evaluated using a synthetic indicator of development, SDG Index and Spillover Index, to obtain and promote the goals of sustainable development. Research methods: comparative analysis; statistical analysis; systematization, generalization. Over the analyzed period, the situation of all Eastern European countries has improved due to the gradual implementation of sustainable development goals. However, the current situation isnot beneficial in Eastern European countries, but the some of them (for example Slovenia and Czech Republic) are very close to completing this status. During analyzed period, a reasonable situation was observed in Estonia, Hungary, Slovakia, Poland, Lithuania, Latvia and Croatia. Despite the significant progress Bulgaria and Romania continue to exist at a disadvantage. The most popular in Eastern Europe are financial resources to support small and medium-sized companies, research and innovation, and a low-carbon economy. As a result of the research, it was found that this analysis can provide further motivation and incentives for appropriate action by East ern European countries to address existing calls. In Eastern Europe, sustainable development should beseen as a goal of development, no less important, namely to reduce contrasts in the quality of life of the population compared to Western European countries.
Keywords: synthetic development indicator; paradigm of sustainable development; sustainable development; sustainable development goals; socioeconomic development